Projected changes in wind speed and wind energy potential over West Africa in CMIP6 models - Akintomide Afolayan Akinsanola; Kehinde O Ogunjobi; Akintayo T Abolude; Seyni Salack (Environmental Research Letters, 2021)
The development of wind energy in West Africa is essential to meet the rising energy needs due to population growth and societal development. However, only few studies have investigated the changes in turbine hub-height wind characteristics over the region under changing climate. This study aims at assessing the impact of climate change on wind power density (WPD) over West Africa using the simulations from the newly developed Coupled Model Intercomparison Project version 6 (CMIP6) models. The CMIP6 near-surface wind speed and directions simulations for the historical climate (1985–2014) were compared with ERA5 reanalysis data using multiple descriptive statistics. Relative to ERA5 reanalysis, the CMIP6 models alongside their multimodel ensemble mean (EnsMean) realistically reproduce the near-surface wind characteristics (i.e. wind speed and directions) across most subregions of West Africa, although noticeable biases still exist. Overall, the CMIP6 EnsMean performs better than most individual models at capturing the near-surface wind speed over the region. Under global warming, we find a robust projected increase (about 70%) in WPD over the Guinea coast subregion of West Africa, especially in June–July–August season. The December–January–February and March–April–May seasons show alternating projected WPD increase and decrease, with predominantly robust projected decrease over the Sahel subregion. The projected increase over the Guinea coast has strong temporal qualities, with the end of the century (2070–2099) changes showing stronger magnitude compared to the mid-century (2040–2069) changes, and thus may provide a commercially viable renewable energy source.